2014
DOI: 10.1186/s40538-014-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural products: an extraordinary source of value-added compounds from diverse biomasses in Brazil

Abstract: The biodiversity of Brazil contains an extraordinary number of compounds from natural products with a wide and complex variety of molecular structures, therefore representing an economic potential in biomasses to be explored. Plant systems are the principal source of medicine and directly contribute to the development of new drugs in addition to agrochemicals, cosmetics, fine chemicals and nutraceuticals. Besides plants, other biomasses can be used as raw material, including marine organisms and microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Due to its antimicrobial activity, PL also has been used for veterinary and agricultural purposes. It has a fertilizing effect on some plants and presents nematocidal, fungicidal, and insecticidal action in the control of pests and plant diseases, and the remediation of soils (Silva and Rodrigues 2014;Silva et al 2017;Theapparat et al 2015;Togoro et al 2014). Melo et al (2017) found promising results in using pyroligneous liquor for the integrated management of plant diseases.…”
Section: Responsible Editor: Giovanni Benellimentioning
confidence: 99%
“…Due to its antimicrobial activity, PL also has been used for veterinary and agricultural purposes. It has a fertilizing effect on some plants and presents nematocidal, fungicidal, and insecticidal action in the control of pests and plant diseases, and the remediation of soils (Silva and Rodrigues 2014;Silva et al 2017;Theapparat et al 2015;Togoro et al 2014). Melo et al (2017) found promising results in using pyroligneous liquor for the integrated management of plant diseases.…”
Section: Responsible Editor: Giovanni Benellimentioning
confidence: 99%
“…The immense diversity of life forms in the ocean correlates with the vast variability of biomaterials present in marine organisms. Thus, there is interest to retain compounds of interest from fishery side products as an ecological approach to acquire high‐value compounds . Marine‐based compounds for materials science are very diverse and have various applications in ceramics, gels, and other biopolymers .…”
Section: Applications Of Mnps In Biotechnology Bioengineering and Pmentioning
confidence: 99%
“…Thus, there is interest to retain compounds of interest from fishery side products as an ecological approach to acquire high‐value compounds . Marine‐based compounds for materials science are very diverse and have various applications in ceramics, gels, and other biopolymers . MNPs have also been important in creating biofuels a new way, namely biodiesel and bioethanol .…”
Section: Applications Of Mnps In Biotechnology Bioengineering and Pmentioning
confidence: 99%
“…Brazil is considered to be the territory with the richest biodiversity in the world [811]; the Cerrado is the second main biome, exhibiting a great diversity of natural plants [9, 12, 13]. The Cerrado is located in the middle west of Brazil, encompassing almost 2 million km 2 that covers 21% of the Brazilian territory [14, 15].…”
Section: Introductionmentioning
confidence: 99%